Appendix 1. Annotated bibliography - Haßler, Björn; Haseloff, Gesine; Adam, Taskeen; Akoojee, S.; Allier-Gagneur, Zoé; Ayika, S.; Bahloul, K.; Kigwilu, P. Changilwa; Costa, D. Da; Damani, Kalifa; Gordon, Rebecca; Idris, A.; et al. (Technical and Vocational Education and Training in Sub-Saharan Africa: A Systematic Review of the Research Landscape, 2020)
This chapter/appendix forms part of the full report: Haßler et al. (2020). Technical and Vocational Education and Training in Sub-Saharan Africa: A Systematic Review of the Research Landscape (1st ed.). VET Repository, Bundesinstitut für Berufsbildung, Bonn, Germany. https://doi.org/10.5281/zenodo.4264612. The document is available under Creative Commons Attribution, and both a PDF and a Word document are avaialable.
ConceptDOI: 10.5281/zenodo.3843382 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3843383 10.5281/zenodo.4290634 2129771:AQFVDKFE
Keywords: Author:Haßler; Author:OpenDevEd; AuthorFirst:Haßler; Björn-CV-OECS; _r:ImportedToMyEducationEvidence; _yl:aa1